Rethinking systemic change: economic evolution and institutions. Discu ssion paper - Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually so und definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of th e research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics new institutional economi cs complexity theory There is a growing interest in these bodies of kn owledge, combined often called New Economic Thinking, and how they aff ect economic development. Hence, while rethinking systemic change, thi s work also contributes to answering the broader question of how marke t systems approaches can contribute to inclusive economic development. The answer, in short, is to shift the focus away from improving trans actions at the micro level towards enabling actors to continuously sha pe an institutional landscape that supports inclusive economic evoluti on. This discussion paper briefly presents the key messages from the l iterature review and seven principles drawing from this literature. Th e principles can be used by market development practitioners, includin g technical advisers in donor organisations, programme designers and t eam leaders, to shape programmes and become more in line with how chan ge happens in the economy. A list of selected references is presented at the end. A technical paper contains a much more detailed discussion of the findings and the principles and an extensive list of reference s. A case study offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).